2022
DOI: 10.15252/embj.2021109202
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian UPF3A and UPF3B can activate nonsense‐mediated mRNA decay independently of their exon junction complex binding

Abstract: Nonsense‐mediated mRNA decay (NMD) is governed by the three conserved factors—UPF1, UPF2, and UPF3. While all three are required for NMD in yeast, UPF3B is dispensable for NMD in mammals, and its paralog UPF3A is suggested to only weakly activate or even repress NMD due to its weaker binding to the exon junction complex (EJC). Here, we characterize the UPF3A/B‐dependence of NMD in human cell lines deleted of one or both UPF3 paralogs. We show that in human colorectal cancer HCT116 cells, NMD can operate in a U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(64 citation statements)
references
References 80 publications
(150 reference statements)
9
55
0
Order By: Relevance
“…Thus, it remains an open question how relevant the individual UPF3 paralogs and their potential NMD activating or repressing function are in different vertebrates and/or different cell types. Interestingly, in a parallel manuscript, Yi et al find that not only human but also mouse UPF3A was able to restore NMD activity in their HCT116 UPF3A‐UPF3B dKO cell line (Yi et al , 2022 ). In case of a general NMD inhibitory function of human or mouse UPF3A, no rescue effect should have been observed, which further questions the proposed broadly acting role of UPF3A as an NMD repressor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it remains an open question how relevant the individual UPF3 paralogs and their potential NMD activating or repressing function are in different vertebrates and/or different cell types. Interestingly, in a parallel manuscript, Yi et al find that not only human but also mouse UPF3A was able to restore NMD activity in their HCT116 UPF3A‐UPF3B dKO cell line (Yi et al , 2022 ). In case of a general NMD inhibitory function of human or mouse UPF3A, no rescue effect should have been observed, which further questions the proposed broadly acting role of UPF3A as an NMD repressor.…”
Section: Discussionmentioning
confidence: 99%
“…Our own work and the work of Yi et al have re‐examined the functions of the human UPF3 paralogs UPF3A and UPF3B (Yi et al , 2022 ). Together, the studies confirmed some previous findings and contradict others, thereby successfully (re‐)defining the role of UPF3 proteins and their functional domains in human cells.…”
Section: Discussionmentioning
confidence: 99%
“…This agrees with reports of a link between CASC3-containing EJCs and UPF3B [ 39 , 47 ]. Consistently, in CASC3 knockdown cells, UPF3B's association with the EJC was reduced, and vice versa CASC3 overexpression led to enhanced EJC–UPF3B association in HeLa cells [ 51 ]. The structure of EJC–UPF3B indicates that the interactions of CASC3 and UPF3B with the EJC core are limited to small regions of the two proteins ( Figure 1E ) [ 49 , 52 ].…”
Section: The Nmd Machinerymentioning
confidence: 88%
“…UPF3B associates with the EJC in the nucleus and is exported with the spliced EJC-bound mRNA, while UPF2 is recruited by UPF3B to the EJC at the nuclear envelope after export [ 49 ]. Recent work suggests a role of CASC3 in promoting the association of UPF3B with the EJC and in enhancing UPF3B-dependent NMD [ 50 , 51 ]. This agrees with reports of a link between CASC3-containing EJCs and UPF3B [ 39 , 47 ].…”
Section: The Nmd Machinerymentioning
confidence: 99%
See 1 more Smart Citation